Durabilitas Campuran Asphalt Concrete-Binder Course (AC-BC) dengan Menggunakan Agregat Tanjungan Lampung Selatan - Zillie, Muhammad Febry; Putra, Sasana; Herianto, Dwi; Sulistyorini, Rahayu (Universitas Lampung, 2023)
Road damage is one of the problems caused by low material quality. The 2018 Bina Marga General Specifications have required material quality for asphalt mixtures, where good quality materials will produce pavement construction with high stability. This research aims to analyze the durability of the AC-BC (Asphalt Concrete-Binder Course) mixture using local materials from PT Sumber Batu Berkah, Tanjungan District, South Lampung Regency without additives based on the Marshall Testing Method. Based on the results of the research, it was found that the effect of soaking time variations of 0.5 hours, 24 hours, 168 hours, and 672 hours with a standard temperature of 60°C, the sample was soaked for a long time would make the stability and durability values smaller. Then obtained IKS value of 91.58% so it has met the minimum Bina Marga Standard of 90% and shows the longer soaking time, the smaller IKS value will obtained. Then for the IDP value is positive which means that the strength decreases by 0.44% during the soaking period so it meets the standard < 1%. And the IDK value of AC-BC mixture is 19.51 where the IDK value has decreased in strength by 19.51% during the soaking time. This is due to the decrease of stability value against the length time of soaking.